Victoria topographic map 1:25 000. 7723-1-3, Drummond - Victoria. Division of Survey and Mapping (Melbourne : Dept. of Crown Lands and Survey, 1982)
Large scale topographic series, relief shown by contours, form lines and spot heights.
Keywords: Drummond (Vic.) -- Maps; Topographic maps